PERAN ORGANISASI MASYARAKAT FBR DALAM MENINGKATKAN KEAMANAN DAN KETERTIBAN LINGKUNGAN SEBAGAI UPAYA PENCEGAHAN PENCURIAN SEPEDA MOTOR DI WILAYAH KAVLING BNI 46 KECAMATAN JATI ASIH KOTA BEKASI - Nisfani Al Azis, Muhammad Viki (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2021)
The Betawi Rempug Forum (FBR) is a Betawi ethnic organization with the majority of its members being Muslim. FBR is ready to work together and assist in maintaining security and peace, especially in the area of Kavling BNI 46. Security and public order is on the decline, especially in the residential Kavling BNI 46, because many residents are anxious about one form of crime that has recently occurred, namely theft cases. especially motorcycle theft. Various efforts made by the authorities and the community itself were unable to stop it. Because these crimes cannot be stopped easily but can only reduce the number of crimes and direct criminals to return as good citizens of society. This study aims to determine the role of FBR in improving environmental security and order as an effort to prevent motorbike theft in the BNI 46 Lot Area, Jati Asih District, Bekasi City. The research method in this study uses a descriptive method with a qualitative research approach. The results showed the quantity and quality of work activities / programs and the role of FBR in improving environmental safety and order had achieved success. That the quality of work activities / programs and also the role of the community organization FBR can be said to have gone very well in reducing the quantity of motorbike theft in the BNI 46 Lot area. In 2018 there were 4 cases and increased to 5 cases in 2019.